Comparative cutting effectiveness of an ultrasonic diamond tip and a high-speed diamond bur. - Lima, L. M.; Motisuki, C.; Corat, E. J.; Santos-Pinto, L. (My University, 2009)
AIM: The aim of this in vitro study was to compare an ultrasonic diamond tip to a high-speed conventional diamond bur regarding the cutting effectiveness in enamel and dentin of human teeth. METHODS: Twenty permanent molars were longitudinally sectioned in the buccal-lingual plane giving 40 specimens, 20 for enamel and 20 for dentin groups. One cavity was performed in each specimen using a spherical diamond tip (83231, CVDentus(R), CVDVale, São José dos Campos, SP, Brazil) coupled with an ultrasound device or a conventional spherical diamond bur (1013, KG Sorensen, São Paulo, Brazil)) coupled with a high-speed turbine. A modified measurement analysis using the Radiocef 4.0 software (Radiocef Memory) was applied to determine the width and the depth of the cavities on scanning electron microscopy (SEM) at x50 magnification micrographs. The features of the cavities and the characteristics of the cutting instruments were also examined under different magnifications by SEM. RESULTS: Statistical analysis by Kruskal-Wallis non-parametric and Dunn post hoc tests (P < or = 0.05) showed that cavities prepared in enamel and dentin with the ultrasonic diamond tip were shallower and narrower than those prepared with conventional diamond bur. The internal walls of cavities prepared in dentin by the ultrasonic diamond tip reproduced the superficial aspect of the diamond, however, scratches were observed in the internal walls of the dentin cut by high-speed conventional diamond bur. CONCLUSIONS: Both instruments were effective in enamel and dentin cutting; however, cavities prepared with a high-speed conventional diamond bur showed more invasive characteristics.